Rapid and sensitive detection of Mycobacterium tuberculosis using the RPA/Cas12f1_ge4.1 system with fluorescence and lateral flow readouts - Zhongliang Deng; Xingyong Weng; Honghua Tang; Tintao Zou; Xuan Zhou; Hangxi Liu; Piaoting Wen; Gemiao Luo; Tian Gan; Jun He (Microbiology Spectrum)
ABSTRACT Tuberculosis remains a major global health threat, with existing detection methods often limited by efficiency and resource demands. Our previous PAM-dependent dsDNA Target-activated Cas12f1 Trans Reporter (PDTCTR) fluorescence sensing platform, while effective for PAM-dependent pathogen detection, was constrained by its reliance on specialized fluorescence equipment and lack of visual output, limiting its use in resource-limited settings. To overcome these limitations, we introduce an innovative RPA/CRISPR-Cas12f1_ge4.1 dual-mode system for rapid Mycobacterium tuberculosis detection. This system combines engineered Cas12f_ge4.1 with recombinase polymerase amplification (RPA), offering both fluorescent and lateral flow detection. It achieves high sensitivity with detection limits of 10 copies/µL (fluorescence) and 100 copies/µL (lateral flow), alongside 100% specificity. In clinical validation, compared with a commercial qPCR kit, the fluorescent and lateral flow approaches demonstrate sensitivities of 94.52% (69/73, 95% confidence interval [CI]: 85.84%–98.23%) and 90.41% (66/73, 95% CI: 80.67%–95.73%), respectively, while maintaining 100% (40/40, 95% CI: 89.09%–100%) specificity and high concordance (kappa values: 0.924 and 0.878). Detection is completed within 1 h, providing a rapid, sensitive, and specific solution for M. tuberculosis identification. This dual-mode capability represents a significant advancement in current tuberculosis diagnostics, enabling both sensitive laboratory confirmation and rapid point-of-care screening. Our versatile and efficient method promises to transform tuberculosis diagnostics, particularly in resource-constrained environments.IMPORTANCETuberculosis (TB) remains a significant global health challenge, demanding rapid and accurate detection for effective management. The innovative RPA/CRISPR-Cas12f1_ge4.1 dual-mode system represents a major advancement in TB diagnostics, offering highly sensitive and specific detection of Mycobacterium tuberculosis DNA. This adaptable system, incorporating both fluorescent and lateral flow detection modes, is designed for use in both advanced laboratories and resource-limited settings. Its high performance, rigorously validated through clinical trials, holds the potential to revolutionize TB diagnosis, particularly in high-burden, low-resource areas. By facilitating earlier treatment and enhancing control of TB transmission, this system could significantly contribute to global efforts in combating this persistent public health threat.